Risk Factors for Extubation Failure in Extremely Low Birth Weight Infants - Shih-Hsin Wang; Jyun-You Liou; Chien-Yi Chen; Hung-Chieh Chou; Wu-Shiun Hsieh; Po-Nien Tsao (Pediatrics and Neonatology)
Although antenatal steroids and early use nasal continuous positive airway pressure (NCPAP) have significantly improved outcomes of neonatal respiratory distress syndrome, intubation with ventilator support is still commonly required in extremely low birth weight (ELBW) infants. The optimal timing of extubation in ELBW infants remains unclear. Methods: We retrospectively analyzed all ELBW preterm infants who were admitted to our neonatal intensive care unit (NICU) from January 2009 to December 2013. Demographic, ventilation, and arterial blood gas analysis results prior to and 2 hours after extubation were collected. Extubation failure was defined as reintubation due to deterioration of respiratory condition within 7 days after extubation. Risk factors for extubation failure were analyzed. Results: In total, 173 ELBW infants were born and admitted to our NICU during these 5 years. Among these 173 infants, 77 (44.5%) used NCPAP only during their hospitalization (20 diagnosed with chronic lung disease (CLD), 25.9%). Among the 95 patients that required intubation, 27 patients expired so extubation was not attempted. Sixteen of 68 (23.5%) survival cases required reintubation within 7 days after extubation. We found that gestational age, birth body weight, and sex ratio did not differ between the successful extubation group and the failed extubation group. Univariate analysis showed that the failed extubation group had a lower arterial pH right before and 2 hours after extubation, with a lower bicarbonate level after extubation. Further multivariate logistic regression analysis revealed an association between poor acid-base homeostasis 2 hours after extubation (pH < 7.3 and HCO3 < 18 mM/L) and extubation failure (odds ratio 4.56 and 6.187 and 95% confidence interval: 1.263∼16.462 and 1.68∼22.791, respectively). Conclusion: This study shows that nearly half of ELBW infants do not require intubation. Among ELBW infants who require invasive ventilator support, those who have lower postextubation arterial pH and bicarbonate levels are at high risk of extubation failure.